SAE Technical Paper Series 2012
DOI: 10.4271/2012-01-1644
|View full text |Cite
|
Sign up to set email alerts
|

In-cylinder Combustion Visualization of a Direct-injection Spark-ignition Engine with Different Operating Conditions and Fuels

Abstract: A direct-injection and spark-ignition single-cylinder engine with optical access to the cylinder was used for the combustion visualization study. Gasoline and ethanolgasoline blended fuels were used in this investigation. Experiments were conducted to investigate the effects of fuel injection pressure, injection timing and the number of injections on the in-cylinder combustion process. Two types of direct fuel injectors were used; (i) high-pressure production injector with fuel pressures of 5 and 10 MPa, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Based on the HRR curves shown, it can be concluded that the shape of HRR in DF combustion is a function of TDC temperature, operating load conditions and the premixed gas-to-air equivalence ratio. Additionally, the HRR curves follow SI combustion behavior more closely [26], suggesting that the premixed turbulent flame front propagation is a dominant mode of combustion.…”
Section: Effect Of φCh4 and Intake Air Temperature (Ttdc)mentioning
confidence: 76%
“…Based on the HRR curves shown, it can be concluded that the shape of HRR in DF combustion is a function of TDC temperature, operating load conditions and the premixed gas-to-air equivalence ratio. Additionally, the HRR curves follow SI combustion behavior more closely [26], suggesting that the premixed turbulent flame front propagation is a dominant mode of combustion.…”
Section: Effect Of φCh4 and Intake Air Temperature (Ttdc)mentioning
confidence: 76%
“…Of these blends, E20 achieved the most optimal specific fuel consumption (SFC). Studies have also shown that ethanol increases flame front speed and early flame development [20,31,32,33]. Improvements in combustion dynamic may increase torque at high rpm.…”
mentioning
confidence: 98%
“…Furthermore, this piston top allows the laser to illuminate the flow inside the cylinder in tumble flow studies [23,24]. Also, it is used to allow the combustion flames to be captured with a high-speed camera in the case of firing operations [38,39]. In optical engine design, the piston top is a necessary component.…”
Section: Application Of the Coupled Finite Element Analysis Methodolo...mentioning
confidence: 99%